"Don't look down on us": Assessing the vulnerabilities of female massage parlor workers in Phnom Penh. Issue 1 (21st January 2020) - Miles, Glenn; Geyer, Theresa; Ding, Rachel; Blasé, Olivia; Clark, Katie
Abstract : Purpose: Although some research has been done with entertainment workers in KTV bars, little has been done to gain a qualitative understanding of the vulnerabilities of masseuse women. This is due to a prevalent focus on girls under 18 years, thereby excluding most masseuses. The purpose of this paper is to understand the reality of life as perceived by Phnom Penh's female masseuses in the lower-priced massage parlors is therefore largely unknown. Design/methodology/approach: In total, 98 female participants completed an interview answering both open and closed questions concerning relationships, stigma and discrimination and personal sexual abuse among other topics. Findings: This study finds that many women working in the massage parlor industry are vulnerable to various threats, including sexual exploitation and abuse. Dependency structures within the massage parlor as well as with their families seem to play a key role in the life situations that can be positive as well as negative, and in some cases both. Research limitations/implications: This is not a prevalence study so all figures are tentative. The women were deeply concerned that they might be stigmatized further so they may not have revealed the extent of their challenges. Practical implications: More research and work with this vulnerable group is vital. They should be recognized as a vulnerable group who have rights. Social implications: The findings provide a baseline evaluation of the vulnerable conditions of the massage industry for women in Cambodia. Specifically, that stigma, discrimination, physical and sexual abuse, as well as a lack of access to education are all vulnerabilities not commonly covered, especially with adult women working in the entertainment industry. Originality/value: Understanding the reality of life as perceived by Phnom Penh's female masseuses in the lower-priced massage parlors is therefore largely unknown so a study of this kind is necessary.